КОНЦЕПЦІЯ ПІДВИЩЕННЯ БЕЗПЕКИ ВУЗЛІВ РОЗПОДІЛЬЧОЇ ЕНЕРГЕТИЧНОЇ ІНФРАСТРУКТУРИ УКРАЇНИ - Мелещук, Д.В. (Інститут електродинаміки Національної академії наук України, 2023)
Methods of increasing the security of the distribution system of the energy infrastructure of Ukraine during its further restoration and modernization are considered. An overview of the relevant issues that arise when the goal is achieved is made. The importance of the problem of protection of electrical substations of the energy distribution infrastructure and the need for appropriate research and development to create an optimal method of protection are indicated. One of the variants of the optimal concept of appropriate protection of the main units of substations is described, which involves the protection of transformers in particular.  References 3, figures 1.